The correct answer is A
I. 6y2 – 23y + 20 = 0
II. 4x2 – 24 x + 35 = 0
I. 2x2 - 9 x + 9 = 0
II. 2y2 - 7 y + 3 = 0
I. 2y2– 19y + 35 = 0
II. 4x2– 16x + 15 = 0
Equation 1: x² - 90x + 2025 = 0
Equation 2: y² - 88y + 1936 = 0
I. 22x² - 97x + 105 = 0
II. 35y² - 61y + 24 = 0
Let 's' represent the sum of the highest root of equations I and III, and 'r' denote the product of the lowest root of equation I and the highest root o...
I. 8x² - 74x + 165 = 0
II. 15y² - 38y + 24 = 0
I. 63x² + 37 x – 40 = 0
II. 15 y² + 29 y + 12 = 0
I). 5p2 - p - 4 = 0
II). q2 - 12q + 27 = 0
I. 12x2 + 22x + 8 = 0
II. 4y2 - y − 3 = 0